Study of the Thermal Properties of Clay-Straw Composite Material for Thermal Insulation of Buildings - Prof. Oumar DIALLO; Dr. Mory COULIBALY; Djiby COULIBALY; Ahmadou Samba TOURE; Prof. Harouna Mamadou BAL; Prof. Salif GAYE, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2025)
Clay is an environmentally-friendly material available throughout Senegal. To reduce the energy consumption of buildings and the emission of greenhouse gases, clay is often used in construction, and natural insulating materials such as straw are combined with it to improve its thermal properties. An experimental transient parallel hot-wire measurement was used to determine the influence of straw addition on the thermal properties of the composite material. The thermal results showed that adding straw to the clay reduced its thermal conductivity by 61%. The clay-straw composite could therefore be an alternative to concrete-based materials for ensuring thermal comfort in buildings.